Relevansi Islam Nusantara sebagai Epistemologi Pancasila Upaya Merangkai Sebab, Menyemai Tanggung Jawab - Majid, Mohamad Arif (Prodi Sosiologi Agama, 2018)
Nusantara Islam is ala Indonesian Islam, a combination of theological values of Islam and Local traditions of Nusantara. The characteristics of Nusantara Islam show local wisdom in Nusantara which does not disobey Islamic teaching, yet they synergize it with local customs all over Indonesia. The coming of Islam in Nusantara did not break nor challenge the local traditions but it enriched and simultaneously Islamized them. The constant contact between local traditions and the Islamic soul resulted in mutual binding and complement to form an excellent character believed and preserved from generation to generation for centuries. Hence, the value had been so close and attached to Indonesian characters. For years such character stayed in the womb of Nusantara Islam and was ready to be born, and then Bung Karno together with the nation founding fathers helped the birth of this nation's value as the foundation of Indonesian Independence. This was the most wanted Pancasila which is believed now to have been left by Indonesians and some faults and deviations in the life of state management and social system occurred. Muslims, therefore, must be responsible for this and take strategic steps at once to face this by carrying out the right and precise Islamic education.